Comparative analyses of the gut microbiome of two sympatric rodent species, Myodes rufocanus and Apodemus peninsulae, in northeast China based on metagenome sequencing - Jing Cao; Shengze Wang; Ruobing Ding; Yijia Liu; Baodong Yuan (PeerJ)
The gut microbiota is integral to an animal’s physiology, influencing nutritional metabolism, immune function, and environmental adaptation. Despite the significance of gut microbiota in wild rodents, the Korean field mouse (Apodemus peninsulae) and the gray red-backed vole (Myodes rufocanus) remain understudied. To address this, a metagenomic sequencing analysis of the gut microbiome of these sympatric rodents in northeast China’s temperate forests was conducted. Intestinal contents were collected from A. peninsulae and M. rufocanus within the Mudanfeng National Nature Reserve. High-throughput sequencing elucidated the gut microbiome’s composition, diversity, and functional pathways. Firmicutes, Bacteroidetes, and Proteobacteria were identified as the dominant phyla, with M. rufocanus showing greater microbiome diversity. Key findings indicated distinct gut bacterial communities between the species, with M. rufocanus having a higher abundance of Proteobacteria. The gut microbiota of A. peninsulae and M. rufocanus differed marginally in functional profiles, specifically in the breakdown of complex carbohydrates, which might reflect their distinct food preferences albeit both being herbivores with a substantial dietary overlap. The investigation further elucidated gut microbiota’s contributions to energy metabolism and environmental adaptation mechanisms. This study aligns with information on rodent gut microbiota in literature and highlights the two understudied rodent species, providing comparative data for future studies investigating the role of gut microbiota in wildlife health and ecosystem functioning.